1974
DOI: 10.1161/01.cir.50.2.395
|View full text |Cite
|
Sign up to set email alerts
|

De Subitaneis Mortibus

Abstract: Disseminated intravascular coagulation was the cause of death of a 19-year-old woman with a lifelong history of paroxysmal atrial tachycardia. Her final illness began with a bout of tachycardia during her second trimester of pregnancy and was then characterized by sustained tachycardia with hypotension, oliguria, and renal failure, with a steadily falling hematocrit in the absence of significant bleeding externally. At necropsy there were numerous platelet and fibrin emboli throughout the heart. Small arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We surmise that the AV node artery in our case was chronically or transiently pressed by the circumferential architecture due to a chronic increase in intracardiac pressure, which may have been caused by degeneration of the cardiac myocytes and/or pulmonary hypertension due to AP abuse. Stenosis of the AV node artery is sometimes the cause of sudden cardiac death (James et al, 1974;Nishida et al, 2000). Accordingly, severe emotional stress experienced while being arrested could produce an increasing pressure load on the heart (Melville and Raftery, 1981;Giannuzzi et al, 1991), and severe fatal mechanical stenosis of the AV node artery could occur subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…We surmise that the AV node artery in our case was chronically or transiently pressed by the circumferential architecture due to a chronic increase in intracardiac pressure, which may have been caused by degeneration of the cardiac myocytes and/or pulmonary hypertension due to AP abuse. Stenosis of the AV node artery is sometimes the cause of sudden cardiac death (James et al, 1974;Nishida et al, 2000). Accordingly, severe emotional stress experienced while being arrested could produce an increasing pressure load on the heart (Melville and Raftery, 1981;Giannuzzi et al, 1991), and severe fatal mechanical stenosis of the AV node artery could occur subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…None had fibrosis of the AVN or His bundle. The authors found 13 other cases of sudden death due to FMH of the AVN artery (17)(18)(19)(20)(21). One patient has a history of third degree AV block and syncope, six had fibrosis of the AVN, His bundle or both and one had an infarct of the His bundle.…”
Section: Fmh Of the Avn Arterymentioning
confidence: 99%